Blended Learning Models: Combining Traditional and Digital Approaches - Refide, Ablyakimova; Ismigul, Toshpulatova (Indonesian Journal Publisher, 2023)
This article elucidates the identification of the most efficacious innovative methods and technologies within the contemporary higher education system. It underscores the significance of electronic education at the tertiary level and delves into the concept of blended learning along with its diverse models, as articulated by various local and international scholars in the existing literature. Additionally, the article explores the integration of cutting-edge technologies to enhance pedagogical approaches, fostering a dynamic and engaging learning environment. It delves into the pivotal role of electronic education in meeting the evolving needs of students, preparing them for the challenges of the digital era. Furthermore, the discussion delves into the diverse models of mixed education, offering a comprehensive overview of the strategies proposed by both local and international scholars in educational literature.